Strengthening Collaboration Networks: Building an Innovation Ecosystem for MSMEs in the Start Up Era - Oktavianna, Rakhmawati; Taha, Roshaiza; Icih, Icih; Kohar, Abdul; Lestari, Baiq Anggun Hilendri; Setiyorini, Wahyu; Hendrayanti, Silvia; Pratama, Aryan Agus; Effriyanti, Effriyanti; Sugiyarti, Listya (Abdimisi, 2023)
Innovation has so far been studied mainly in high-tech companies, but MSMEs are no less able to innovate in their businesses. MSMEs carry out innovations, especially those related to the market, such as meeting customer demands or competing with competitors. Their biggest challenge in innovating is selling variations that are easy to imitate because competitors are very quick to imitate. However, MSMEs must remain focused on innovation, one way is by collaborating to improve their business. At the community service held on Thursday 2 May 2024, together with several universities both from within and outside the country, we lecturers provided knowledge on how MSMEs can improve their businesses through collaboration. The MSMEs who attended were also able to share what obstacles they had faced so far. In the future, it is hoped that this service to the community will continue and be sustainable. Abstrak Inovasi selama ini telah banyak dipelajari terutama di perusahaan-perusahaan teknologi tinggi, namun Usaha Mikro, Kecil, dan Menengah (UMKM) juga tidak kalah mampu untuk berinovasi dalam bisnis mereka. UMKM melakukan inovasi, terutama yang berkaitan dengan pasar, seperti memenuhi permintaan pelanggan atau bersaing dengan kompetitor. Tantangan terbesar mereka dalam berinovasi adalah menjual variasi yang mudah ditiru karena kompetitor sangat cepat menirunya. Namun, UMKM harus tetap fokus pada inovasi, salah satu cara adalah dengan berkolaborasi untuk meningkatkan bisnis mereka. Pada kegiatan pengabdian masyarakat yang dilaksanakan pada hari Kamis, 2 Mei 2024, bersama dengan beberapa universitas baik dari dalam maupun luar negeri, kami para dosen memberikan pengetahuan tentang bagaimana UMKM dapat meningkatkan bisnis mereka melalui kolaborasi. UMKM yang hadir juga dapat berbagi kendala yang mereka hadapi sejauh ini. Di masa depan, diharapkan pengabdian kepada masyarakat ini dapat berlanjut dan berkelanjutan. Kata Kunci: Memperkuat Kolaborasi, Ekosistem Inovasi, dan Era Start-Up.